Students’ Perceptions on the Use of Hot Potatoes Exercises in English Subject - David Geba Abi Anandi; Marchellina Wijaya (LPPM Universitas Advent Indonesia, 2024)
This study aimed to examine students’ perceptions on the use of “Hot Potatoes” exercises in practicing recount text material in English Subject. The research questions in this research are: 1) What are the students’ perceptions on the use of “Hot Potatoes” exercises in practicing recount text material in English Subject? and 2) What are the advantages and disadvantages of using “Hot Potatoes” exercises in practicing recount text material in English Subject? The method used was a descriptive qualitative method. The participants of this research were 29 students of a senior high school in Tangerang. The findings show the students have positive responses towards the use of “Hot Potatoes” exercises in practicing recount text material in English Subject. The conclusions are the students give positive responses on the use of “Hot Potatoes” exercises in practicing recount text material in English Subject. The advantages of using Hot Potatoes exercises are related to understandable and fun questions, and instructions, the motivation improvement in English learning, the interactivity, and the variety of English exercises. Lastly the disadvantages of using “Hot Potatoes” exercises are the need for internet connection to access the exercises, and the availability of devices, and the inability of some features.